Analisis Faktor Yang Mempengaruhi Penggunaan Alat Kontrasepsi Implan di Puskesmas Wates - Nugraheni, Hermita; Rahmatiningtyas, Indah; Pratamamningtyas, Susanti; Sendra, Eny (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2025)
Abstract Indonesia is one of the countries with the highest population in the world, which is in fourth place. The government implemented the Family Planning program to prevent very rapid population growth. Implants are contraceptives intended to prevent pregnancy, which are considered effective and not permanent. Implants can last for three to five years with a failure rate of only 0.05 out of 100 women who use them, implants are up to 99 percent effective. Age, parity, education, and occupation are some of the factors that influence a person's choice of contraception method. This research was conducted to evaluate variables that contribute to the use of implantable contraceptives at the Wates Community Health Center. This research method uses a cross sectional research design with a retrospective approach. Samples were taken using a simple random sampling technique as many as 72 people. The analysis test used is the chi – square test. The results showed that age and occupation had no effect on the use of contraceptive implants. On the other hand, education level and number of children (parity) are related to the use of contraceptive implants. It is hoped that health services can improve health education regarding contraceptive methods, especially implants. Keywords: Factors, Implant Contraceptive Selection